Bent‐But‐Not‐Broken: Reactive Metal‐Organic Framework Composites from Elastomeric Phase‐Inverted Polymers. (16th September 2020) - Peterson, Gregory W.; Mahle, John J.; Tovar, Trenton M.; Epps, Thomas H.
Abstract: A phase inversion process is used to fabricate composite beads from the metal–organic framework (MOF) UiO‐66‐NH2 and the elastomeric block copolymer poly(styrene‐ block ‐ethylene‐ ran ‐butylene‐ block ‐styrene) (SEBS) for improved performance over activated carbon‐based protective textiles. Textiles incorporating the best MOF‐composite materials reduced steady‐state permeation of the chemical warfare agent (CWAs) simulant, 2‐chloroethyl ethyl sulfide (CEES), by ≈60% versus activated carbon cloth. Additionally, the protection capabilities of the composite beads could be further tuned by adjusting bead size—textiles fabricated from smaller composite beads show enhanced diffusional properties whereas textiles generated from larger beads maximize protective capacity. The elastomeric beads also do not exhibit any attrition when subjected to a hardness test, whereas traditional pressing techniques result in materials with only a 20% retention of particle size. Furthermore, composites with increasing MOF content result in enhanced chemical capacity and reactivity, with the best composite outperforming activated carbon cloth against the CWAs soman (91% versus 17% reacted, respectively) and mustard (97% versus 0% reacted, respectively) over 24 h. The 80 wt% samples also have ≈1.4 and 2.2× higher adsorption capacity for soman and CEES, respectively, versus carbon cloth. Finally, mixing multiple MOFs results in optimal composites for the simultaneous filtration of chlorine and ammonia. Abstract : Composite beads consisting of the metal‐organic framework UiO‐66‐NH2 and the polymer poly(styrene‐ block ‐ethylene‐ ran ‐butylene‐ block ‐styrene), fabricated from phase inversion, enable new personal protective equipment such as reactive suits and enhanced filters. Composites have better reactivity and more protection than activated carbon while significantly reducing particle attrition in a "bend‐but‐not‐break" strategy.